Foundations of Professional Counseling: Counselor Personality, Ethics, Processes, and Media Innovation - Nabila Atika Ajra; Amirah Diniyati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article discusses personality aspects, ethics, counseling processes, and counseling media as essential components that determine the effectiveness of professional counseling services. The background of this study is based on the need for counselors to understand the dynamics of the counselor–client relationship in a holistic manner, including personal characteristics and ethical guidelines that underpin counseling practice. The focus of the discussion includes the role of counselor and client personality, the importance of the therapeutic alliance, fundamental counseling ethical principles, systematic stages of the counseling process, and the use of media as supportive tools for intervention. The method applied in this article is a literature review by examining various scientific sources, journals, and relevant references related to counseling and psychological guidance. The findings indicate that counselor personality traits such as empathy, genuineness, emotional stability, and unconditional positive regard significantly influence counseling success. Furthermore, the implementation of ethical principles such as confidentiality, client autonomy, informed consent, and justice serves as the main foundation for maintaining professionalism. The use of counseling media, including visual, audio, therapeutic play, and digital technology, also enhances communication and intervention effectiveness according to client needs. In conclusion, an integrative understanding of personality, ethics, counseling processes, and media is a crucial foundation for improving the quality of counseling services that are effective, safe, and respectful of client dignity.